(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Research Background: Job satisfaction helps to improve the performance of workers on both criteria, whether it is qualitative or quantitative. Satisfied workers are easily motivated and have an interest in their work. In this study, an investigator has focused on finding out the impact of region and gender differences on the job satisfaction of doctors. Objectives: The study objective was, to find out the impact of region and gender differences on job satisfaction of doctors. Other, objective was, to study the significant difference in level of job satisfaction among the male and female urban as well as rural doctors. Procedure: The study one hundred twenty samples were selected from doctors in the State of Maharashtra. The sample age range was between 35 and 60 years. The study type of region and type of gender were independent variable and level of job satisfaction was dependent variable. The purposive sampling technique was used for the selection of the samples. The study Job Satisfaction Scale developed by Dr. Amar Singh and Dr. T. R. Sharma has been used for data collection. Conclusions: It is concluded that, insignificant difference found in job satisfaction among the urban and rural doctors. The female and female employees have found equal job satisfaction than male doctors. There was no significant difference found in job satisfaction among the urban male and female as well as rural male and female doctors. As per the manual, urban and rural, male and female doctors are found extremely satisfied with their job. Application: The present study findings can be beneficial and helpful for counselors, society member, doctors, and psychologists to understanding impact of region and gender differences on job satisfaction of individuals. The study will help us to understand the impact of the region and gender on the level of job satisfaction of doctors.